'Making space': a study into the use of mindfulness for alternative school teachers. Issue 2 (8th April 2019) - Preston, Kim; Spooner-Lane, Rebecca
Abstract: As teachers seek to educate and transform lives, often with limited resources and time, they can experience varying levels of stress and emotional exhaustion, particularly if effective emotion regulation strategies are not employed. The experience of teacher stress may be heightened in alternative schools that provide educational opportunities for students who present with complex needs and are 'at-risk' of withdrawing from the conventional school system. This case study explored the perceived outcomes of a 6-week school-based mindfulness program to manage stress and support the emotion regulation of four teachers at a metropolitan Australian alternative school. The study took a mixed-methods approach to data collection, which included self-report questionnaires, interview responses and journal reflections. A number of limitations, such as small sample size and lack of experimental design, had an impact on the generalisability of the study's findings. However, a range of beneficial outcomes emerged in association with the mindfulness program, revealing that participants experienced increased levels of both mindfulness and emotion regulation ability, in conjunction with decreased stress and emotional exhaustion levels.